Influence of Zis Funds, Education, Health and Entrepreneurship on the Achievement of Sustainable Development Goal 1 - Satriah Satriah; Muliati Muliati; Latifah Sukmawati Yuniar; Andi Chairil Furqan (SAINTIS Publishing, 2025)
This study investigates the influence of Zakat, Infaq, and Sadaqah (ZIS), education, health, and entrepreneurship on poverty alleviation in Indonesia, particularly in supporting the achievement of Sustainable Development Goal 1 (No Poverty). A quantitative approach was employed using secondary data from the National Amil Zakat Agency of the Republic of Indonesia (BAZNAS RI) and the Central Statistics Agency (BPS) for the 2021–2024 period. The data were analyzed through multiple linear regression with a panel data model. The results indicate that ZIS acceptance has a significant negative relationship with poverty levels, implying that higher ZIS collection and distribution can effectively contribute to poverty reduction. Meanwhile, school participation rates as an indicator of educational attainment show no significant impact on poverty reduction, suggesting that improvements in education quality and relevance are still needed to enhance its economic effect. Life expectancy, representing health indicators, demonstrates a significant negative influence, highlighting the essential role of better healthcare access and quality in reducing poverty. On the other hand, entrepreneurship, measured by the number of Micro and Small Enterprises (MSEs), exhibits a significant positive relationship with poverty, which may reflect challenges such as limited access to financing, low business literacy, and weak competitiveness among small entrepreneurs. These findings emphasize the importance of strengthening ZIS management, enhancing health services, and adopting sustainable strategies in education and entrepreneurship development. This study provides important insights for policymakers, zakat institutions, and communities in formulating effective strategies to accelerate poverty alleviation and achieve Sustainable Development Goal 1 in Indonesia.